"Watch Over Us Sweet Angels": How Loved Ones Remember Babies in a Hospital Memory Book. (September 2016) - Cadge, Wendy; Fox, Nicole; Lin, Qiong
This article considers how parents constructed social identities for babies who died before, at, or shortly after birth between 1992 and 2008 at Overbrook Hospital, a large academic medical center in the northeastern United States. We find that parents constructed their own and their children's social identities through deeply embodied shared senses of physicality, through processes of naming, and with a deep awareness of what they imagined would be ongoing relations. For many, these ongoing relations took place with an eye toward heaven. We situate our findings in historical context and draw out their theoretical implications for contemporary scholarship.